Damage and failure modelling of carbon and glass 2D braided composites - Fouinneteau, M. R. C. (Cranfield University, 2006)
Composite materials have been increasingly used in the past two decades since they offer significant potential weight reduction, part design flexibility and improved specific mechanical performance compared to traditional metals. For specific applications, braid reinforced composites offer better near net shape part and manufacturing flexibility than conventional unidirectional laminates, albeit at the expense of slightly lower in-plane stiffness and strength. Furthermore, for impact and crash applications, which is the emphasis of this thesis, their tow waviness and interlocking can offer excellent damage tolerance and energy absorption. In this work, heavy tow (24k) biaxial carbon and glass braided preforms were used to manufacture coupons and beam structures to undertake an extensive testing campaign to characterise different damage and failure mechanisms occurring in braided composites. Due to large shear deformation and surface degradation, non conventional measurement techniques based on marker tracking and Digital Image Correlation were successfully used to measure strains in the damaging material. The modelling of braided composites was conducted using the meso-scale damage approach first proposed by P. Ladevèze for unidirectional composites. The calibration of an equivalent braid unidirectional ply was achieved using the experimental results obtained for different braided coupons. Furthermore, failure mechanisms observed experimentally, such as tow stretching and fibre re-orientation occurring during loading history, were integrated into the model. A new unidirectional ply formulation was subsequently implemented into the explicit finite element code PAM-CRASHTM. Validation of the new model using single element, coupons and beams were conducted that provided a satisfying correlation between experimental tests and numerical predictions.